Biodiversity of Hoverflies (Diptera: Syrphidae) in Syria and their Importance as Pollinators to some Crops (Latakia University Journal -Biological Sciences Series, 2023)
Insects contribute to pollinate a large number of wild plants. Around 35% of crops partially of completely depend in their pollinations upon insects. The value of crops pollinated by insects is estimated by USD$ 361 billion around the world. Diptera is the second largest order of insects visiting flowers after order hymenoptera. Diptera includes around 30 families; Syrphidae is one of the most dipteran families in diversity, and syrphid species contributing to pollinate a number of crops. This study showed the ecological and economic importance of syrphids, and it aimed to survey syrphid species registered up to date in Syria. Also, it aimed to show their importance as pollinators to some crops. More than 45 species of Syrphidae were documented in Syria; eight of them have a wide geographical distribution, and it is thought to play a key role as pollinators to some crops in Syria. They are suggested to be studied in more details in later studies.